Alkaline Salt Inhibits Seed Germination and Seedling Growth of Canola More Than Neutral Salt - Wang, Weichao; Zhang, Fenghua; Sun, Lupeng; Yang, Lei; Yang, Yang; Wang, Yajuan; Siddique, Kadambot H. M.; Pang, Jiayin (Frontiers in Plant Science, 2022)
Salinity is a major constraint to crop growth and productivity, limiting sustainable agriculture production. Planting canola (Brassica napus L.) variety with salinity-alkalinity tolerance as a green manure on the large area of salinity-affected land in Xinjiang could alleviate feed shortage. To investigate the differential effects of neutral and alkaline salt stress on seed germination and seedling growth of canola, we used two salts at varying concentrations, i.e., NaCl (neutral salt at 100, 150, and 200 mM) and Na2CO3 (alkaline salt at 20, 30, and 40 mM). To further explore the effects of Na+ and pH on seed germination, we included combined of NaCl (0, 100, 150, and 200 mM) and pH (7.1, 8.0, 9.0, 10.0 and 11.0). Shoot growth was promoted by low concentrations of NaCl and Na2CO3 but inhibited at high salt concentrations. Given the same Na+ concentration, Na2CO3 inhibited seed germination and seedling growth more than NaCl. The results showed that the main factor affecting seed germination and seedling growth is not pH alone, but the interaction between pH and salt ions. Under NaCl stress, canola increased the absorption of K+, Ca2+, and Mg2+ in roots and K+ in leaves. However, under Na2CO3 stress, canola maintained a high K+ concentration and K+/Na+ ratio in leaves and increased Ca2+ and Mg2+ in roots. Our study showed that alkaline salts inhibit canola seed germination and seedling growth more significantly than neutral salts and salt species, salt concentration and pH significantly affected on seed germination and seedling growth. However, pH affected seed germination and seedling growth mainly through an interaction with salt ions.